GLOBALLASHUV JARAYONIDA MEDIATA’LIMNI RIVOJLANTIRISH - Egamqulova Shamsiyabonu Jamshid qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, in the context of globalization, in the context of globalization, the conditions, problems and prospects of the development of media significociate were explained. The main purpose of the study is to increase medical community in the information society, protection against misconceptions and improving the modern education system in the information society. The article in the article is the theoretical foundations of medialim, the impact of globalization in this area, as well as the basic barriers to the practice of media